Note on alternative methods of logistic projection - McCarthy, C (Economic & Social Studies, 1974)
Engel curves exhibiting high income elasticities at low levels of income which then decline with income to produce finite per capita saturation levels have been widely used in studies of consumer durable goods (Brown and Deaton). The three parameter logistic growth function is one of several forms which satisfy these requirements and in its numerous applications to problems in biology and epidemiology an estimation method based on the logit transformation is popular (Berkson). A simpler and less onerous method based on the observed rate of growth of per capita consumption is common in studies using the logistic to predict the level of ownership of motor vehicles. It appears however that the logit method should also be used in the latter application of the function.
Keywords: Mathematics; Methods